2006
DOI: 10.1021/jo061158q
|View full text |Cite
|
Sign up to set email alerts
|

Mn-Mediated Coupling of Alkyl Iodides and Chiral N-Acylhydrazones:  Optimization, Scope, and Evidence for a Radical Mechanism

Abstract: Stereoselective radical additions have excellent potential as mild, nonbasic carbon-carbon bond constructions for direct asymmetric amine synthesis. Efficient intermolecular radical addition to C=N bonds with acyclic stereocontrol has previously been limited mainly to secondary and tertiary radicals, a serious limitation from the perspective of synthetic applications. Here, we provide full details of the use of photolysis with manganese carbonyl to mediate stereoselective intermolecular radical addition to N-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 68 publications
0
76
0
Order By: Relevance
“…Friestad has shown that manganese-mediated addition of alkyl radicals to chiral hydrazones occurs with excellent yields and diastereoselectivity. 271 The reaction tolerates a range of primary and secondary iodides as radical precursors, but fails to furnish any product with allyl, benzyl or tert-butyl bromides. The structure of the radical acceptor appears to be unimportant, and even a-branched alkyl imino compounds react in good yields.…”
Section: Radical Additions To C]x Bondsmentioning
confidence: 99%
“…Friestad has shown that manganese-mediated addition of alkyl radicals to chiral hydrazones occurs with excellent yields and diastereoselectivity. 271 The reaction tolerates a range of primary and secondary iodides as radical precursors, but fails to furnish any product with allyl, benzyl or tert-butyl bromides. The structure of the radical acceptor appears to be unimportant, and even a-branched alkyl imino compounds react in good yields.…”
Section: Radical Additions To C]x Bondsmentioning
confidence: 99%
“…The manganese carbonyl reagent proved to be a dramatic improvement [31]. For ethyl iodide addition to 8a (Table 2.6), irradiation (300 nm) with Mn 2 (CO) 10 using InCl 3 as a Lewis acid furnished the ethyl adduct in 85% yield, much higher than with triethylborane or hexamethylditin.…”
Section: Manganese-mediated Radical Additionmentioning
confidence: 99%
“…Manganese-Mediated Coupling with Multifunctional Precursors 2.2.6.1 Hybrid Radical-Ionic Annulation Interestingly, the 3-chloro-1-iodopropane addition (Table 2.6, entry 9) led exclusively to pyrrolidine 37 (Scheme 2.4); none of the acyclic adducts was found [31]. Presumably, radicaladdition wasfollowedbyin situ S N 2-type cyclization.…”
Section: 26mentioning
confidence: 99%
See 1 more Smart Citation
“…12 In our prior work on radical addition reactions of chiral Nacylhydrazones, we found that Mn-mediated additions of alkyl iodides to these CN acceptors proceed via addition of free carbon-centered radicals rather than organomanganese species. 13 The alkyl radicals are generated via a well-precedented halogen atom transfer from alkyl iodide to pentacarbonylmanganese radicals formed on photolysis of Mn 2 (CO) 10 . 14 The synthetic utility of these reactions is enhanced by their functional group tolerance; numerous examples illustrate compatibility with free hydroxyls, esters, silyl ethers, and alkyl chlorides.…”
Section: ■ Introductionmentioning
confidence: 99%